Undrained behavior of embankments on New Liskeard varved clay / by Suzanne M. Lacasse, Charles C. Ladd, Alex K. Barsvary. - Lacasse, Suzanne M.; Ladd, Charles C. (Charles Cushing); Barsvary, A. K.; Massachusetts Institute of Technology. Department of Civil Engineering. Constructed Facilities Division.; Massachusetts. Department of Public Works.; United States. Federal Highway Administration.; National Research Council (U.S.). Transportation Research Board. Annual Meeting 1976 : Washington, D.C.) (Tufts University. Tisch Library., 2019)
1 online resource (iii, 55 leaves) : illustrations.; "Paper to be presented to the 1976 annual meeting of the Transportation Research Board."; "Prepared for Commonwealth of Massachusetts, Department of Public Works in cooperation with U.S. Department of Transportation, Federal Highway Administration"--Cover.; "Order No. 521"--Cover.; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.